Toxoplasma encephalitis in HIV/AIDS patients in Prof. Dr. I.G.N.G. Ngoerah General Hospital, Bali, Indonesia - Suryapraba, Anak Agung Ayu; Sintarani, Cokorda Istri Dyah; Vania, Aurelia; Ni Made Susilawathi; Anak Agung Raka Sudewi (Indonesian Journal of Biomedicine and Clinical Sciences, 2024)
Toxoplasma gondii, an opportunistic infection in HIV/AIDS patients, is an obligate intracellular parasite that causes toxoplasma encephalitis (TE). The symptoms of TE range from subacute focal or global neurologic impairments to neuropsychiatric disorder, and infectious mass lesions. In clinical practice, presumptive diagnosis, including clinical syndrome, finding single or multiple brain lesions on neuroimaging evaluation are preferred. This study aimed to identify neurologic and radiologic characteristics of HIV/AIDS patients with TE in Prof. Dr. I.G.N.G Ngoerah Hospital, Denpasar, Bali. It was a retrospective study using medical records of patients with TE from January 2018 to December 2021. Of 122 subjects, 66.4% were male and 33.6% were female, age ranged from 19-59 y.o. with a median of age 33 y.o., and the CD4 count median was 29.5 cell/mm3. Decreased consciousness was the most prevalent clinical symptom in 40.2% of subjects followed by headache in 18.9% of subjects. A structural lesion in neuroimaging was primarily found in the basal ganglia area of the brain (44.3%). The fatality rate (30.3%) was significantly associated with decreased consciousness, higher leukocyte levels, and a higher neutrophil-to-lymphocyte ratio (p<0.05). Diagnosis of TE should be considered in immunocompromised young adults with subacute onset of focal and/or global neurological deficit and neuroimaging results showing hypodense lesion, particularly with ring-like enhancement, in thebasal ganglia and corticomedullary junction area of the brain. An altered state of consciousness and NLR can indicate poor outcomes in HIV/AIDS patients with TE.